The Peptidyl-Prolyl cis-trans isomerase, Pin1, associates with Protein Kinase C θ via a critical Phospho-Thr-Pro motif in the V3 regulatory domain - Anto, Nikhil Ponnoor; Muraleedharan, Amitha; Nath, Pulak Ranjan; Sun, Zuoming; Keasar, Chen; Livneh, Etta; Braiman, Alex; Altman, Amnon; Kong, Kok-Fai; Isakov, Noah (Frontiers in Immunology, 2023)
Protein kinase C-θ (PKCθ) regulates essential functions required for T cell activation and proliferation. Previously, we provided a mechanistic explanation for the recruitment of PKCθ to the center of the immunological synapse (IS) by demonstrating that a proline-rich (PR) motif within its regulatory domain V3 region in is necessary and sufficient for PKCθ IS localization and function. Herein, we highlight the importance of Thr335-Pro residue in the PR motif, the phosphorylation of which is key in the activation of PKCθ and its subsequent IS localization. We demonstrate that the phospho-Thr335-Pro motif serves as a binding site for the peptidyl-prolyl cis-trans isomerase (PPIase), Pin1. Mutagenesis of PKCθ-Thr335-to-Ala abolished the ability of PKCθ to interact with Pin1, while Thr335 replacement by a Glu phosphomimetic, restored PKCθ binding to Pin1, suggesting that Pin1-PKCθ association is contingent upon the phosphorylation of the PKCθ-Thr335-Pro motif. Similarly, the Pin1 mutant, R17A, failed to associate with PKCθ, suggesting that the integrity of the Pin1 N-terminal WW domain is a requisite for Pin1-PKCθ interaction. In silico docking studies underpinned the role of critical residues in the Pin1-WW domain and the PKCθ phospho-Thr335-Pro motif, to form a stable interaction. Furthermore, TCR crosslinking in human Jurkat T cells and C57BL/6J mouse-derived splenic T cells promoted a rapid and transient formation of Pin1-PKCθ complexes, which followed a T cell activation-dependent temporal kinetic, suggesting a role for Pin1 in PKCθ-dependent early activation events in TCR-triggered T cells. PPIases that belong to other subfamilies, i.e., cyclophilin A or FK506-binding protein, failed to associate with PKCθ, indicating the specificity of the Pin1-PKCθ association. Fluorescent cell staining and imaging analyses demonstrated that TCR/CD3 triggering promotes the colocalization of PKCθ and Pin1 at the cell membrane. Furthermore, interaction of influenza hemagglutinin peptide (HA307-319)-specific T cells with antigen-fed antigen presenting cells (APCs) led to colocalization of PKCθ and Pin1 at the center of the IS. Together, we point to an uncovered function for the Thr335-Pro motif within the PKCθ-V3 regulatory domain to serve as a priming site for its activation upon phosphorylation and highlight its tenability to serve as a regulatory site for the Pin1 cis-trans isomerase.